Salvadoran unconventional renewable energy cluster - Cladellas Romero, Camila; Umaña Trujillo, Carlos Rodolfo; Zepeda González, Daniel Antonio; Benavides Castro, Marian (Empresa y Sociedad, 2024)
Unconventional Renewable Energy (URE) in El Salvador is a form of energy whose sources are not exhaustible such as sun, wind, sea, earth, heat, and biomass. Developing an energy cluster will boost not only the sector, but also the related industries and implicitly the competitiveness of the country, thereby improving in long term the quality of life of its inhabitants and the environment.